2021
DOI: 10.3389/fpsyg.2021.667235
|View full text |Cite
|
Sign up to set email alerts
|

Identity Functioning and Eating Disorder Symptomatology: The Role of Cognitive Emotion Regulation Strategies

Abstract: Introduction: Adolescence is the most critical life period for the development of eating disorder (ED) symptomatology. Although problems in identity functioning and emotion dysregulation have been proven important risk and maintaining factors of ED symptomatology, they have never been integrated in a longitudinal study.Methods: The present study is part of the Longitudinal Identity research in Adolescence (LIA)-study and aimed to uncover the temporal interplay between identity functioning, cognitive emotion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 99 publications
7
14
0
Order By: Relevance
“…There was no prospective association between identity confusion and drive for thinness. Finally, a recent study by Verschueren and colleagues in Belgian adolescents and emerging adults found that identity synthesis and confusion predicted eating disorder symptoms one and two years later (Verschueren et al, 2021 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There was no prospective association between identity confusion and drive for thinness. Finally, a recent study by Verschueren and colleagues in Belgian adolescents and emerging adults found that identity synthesis and confusion predicted eating disorder symptoms one and two years later (Verschueren et al, 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…There was some evidence that depression, anxiety and eating disorder symptoms impact identity development, such that elevated symptoms were associated with identity development difficulties (i.e., low identity synthesis/high identity confusion) later in adolescence (Hatano et al, 2020 ; Schwartz et al, 2012 ; van Doeselaar et al, 2018 ; Verschueren et al, 2018 ; Verschueren et al, 2021 ). Preliminary evidence indicated that effects may differ according to identity domain (i.e., depressive symptoms associated with later educational synthesis, but not interpersonal synthesis) (van Doeselaar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the patients' narrative memory about safety, emotional regulation, and loving kindness seems to be associated with the somatic memory of comfort through a special food. However, the perpetration of an uncontrolled mode of eating would seem to be connected to the lack of an emotional awareness about the meaning of that gesture and its compulsive search or to the underlying need for comfort and kindness (Verschueren et al, 2021). In these scenarios, communication is strongly connected to the feeding.…”
Section: Attachment and Eating Disorders: From Controlling Others To Self-regulationmentioning
confidence: 99%
“…Anorexia nervosa (AN), bulimia nervosa (BN), binge eating disorder (BED), and other eating disorders (EDs) are characterized by poor awareness and emotional regulation in the form of “embodied acts” used to cope with internal and external demands that are perceived as overwhelming and stressful ( Cook-Cottone, 2006 ; Verschueren et al, 2021 ). In some cases, self-assessment is dependent on body shape and weight, leading to persistent dissatisfaction and concerns about one’s worth and body image.…”
Section: Introductionmentioning
confidence: 99%